Preparation of superhydrophobic and superoleophilic polyurethane foam for oil spill cleanup. Issue 11 (1st November 2021) - Li, Hao; Lin, Shaohui; Feng, Xianshe; Pan, Qinmin
Abstract: Preparation, characterization and applications of a novel polyurethane based superhydrophobic and superoleophilic absorbent were studied for the purpose of oil-spill cleanup or water-oil/organic solvent separation. Porous superhydrophobic polyurethane foam was synthesized, followed by a one-step reaction to incorporate copper oxide nanoparticles (nano CuO) and n-hexadecylamine (HDA) onto the surface framework of the polyurethane foam with the aids of oxidative self-polymerization of dopamine. The morphology, thermal stability, and surface wettability of the modified polyurethane foam were characterized by scanning electron microscope, infrared spectroscopy, thermogravimetry, and water contact angle instrumentation. The water contact angle and water sliding angle of the foam up to 153° and 6° respectively, indicating that the modified polyurethane foam had good superhydrophobicity. It was demonstrated that the absorption capacity of the foam for oils/organic solvents was up to 45 times its own weight. The oils/organic solvents absorbed in the foam could be easily recovered by simply pressing, and an oil absorption capacity of higher than 90% was retained after 50 cycles of usage. This study provided a feasible strategy for the preparation of superhydrophobic and superoleophilic foams for water-oil/organic solvent separation. Graphical Abstract: UF0001